OP06 Well London: Results of a Cluster-Randomised Trial of a Community Development Approach to Improving Health Behaviours and Mental Wellbeing in Deprived Inner-City Neighbourhoods. (17th September 2012) - Phillips, G; Hayes, R; Bottomley, C; Petticrew, M; Watts, P; Lock, K; Clow, A; Draper, A; Moore, D; Schmidt, E; Tobi, P; Lais, S; et al.
Abstract : Background: Few public health interventions combining modification of the social and built environment with individual-level health promotion have been robustly evaluated in the UK. Well London is an assets-based community development programme designed to improve physical activity, healthy eating and mental wellbeing in highly deprived inner-city communities. The programme, delivered between 2007 and 2011, comprised a mix of projects delivering traditional health promotion, community development and changes to the physical neighbourhood environment. The objectives of the study are to: (i) determine the effectiveness of Well London for improving healthy eating, physical activity and mental wellbeing in deprived inner-city communities; (ii) examine the effects in population subgroups linked to health inequalities in the UK. Methods: We used a pair-matched, cluster-randomised trial with 20 control neighbourhoods matched within London boroughs to 20 programme delivery neighbourhoods. The trial outcomes in adult residents (aged ≥16 years) were collected using a structured electronic household survey, administered by fieldworkers to 100 randomly sampled residents in each intervention and control neighbourhood. The main outcome measures were: physical activity: meeting UK Chief Medical Officer-recommended five sessions of 30 minutes moderate intensity activity per week (self-report International Physical Activity Questionnaire); healthy eating: eating at least five portions of fruit/vegetables per day (food frequency questionnaire from the Health Survey for England); and mental wellbeing: abnormal score on 12-item General Health Questionnaire; Warwick Edinburgh Mental Wellbeing Scale score. Results: The baseline survey in 2008 showed that the intervention and control populations are comparable on socio-demographic/economic characteristics and primary trial outcomes. At baseline, 37% of adults met the five-a-day (healthy eating), 60% met the five-a-week (physical activity), and 18% reported experiencing anxiety or depression. Results from the follow-up survey will be available in April 2012. We will present the effects of Well London on the primary outcomes and subgroup analyses by gender, age, ethnicity and level of education. Conclusion: In a health system where less than 1% of the research budget is spent on primary preventive interventions for non-communicable diseases, robust evidence about the effectiveness and cost-effectiveness of upstream interventions is essential for action on health inequalities and reductions in healthcare spending recommended by the Marmot Review (2010) and the Wanless report (2004).